Reduction induced by ion beams: hydrogenation of nitrogen-containing heterocycles and quinones in molecular secondary ion mass spectrometry - Hand, Owen W; Detter, Lisa D; Lammert, Stephen A; Cooks, R. Graham; Walton, Richard A (Journal of the American Chemical Society, 1989)
Hydrogenation of N-containing heteroaromatic compounds occurs when solid samples, in the presence of metals with low work functions ({<=}4.5 eV) and low first ionization energies as the free atoms, are subject to bombardment by low-flux ({<=} 10{sup {minus}7} A/cmsup 2), high-energy (5 keV) argon ions. The molecules accept 2 or 3 hydrogens and are observed as (M + 2H){sup {center dot}+} or (M + 3H){sup +} ions. Hydrogenation is observed by using the neat compounds supported on Ti, Ag, Pb, Al, In, Mg, and Gd substrates but is not observed when Pt, Ni, Au, graphite, or Cu substrates are employed. The role of the former metals with low work functions (and low ionization energies) is believed to be the production of low-energy electrons needed to initiate the reductions. Hydrogenation is also observed upon ion bombardment when the compounds are admixed with proton-rich solid matrix (NHsub 4Cl, p-toluenesulfonic acid, C(CHsub 2OH){sub 4}, oxalic acid) supported on graphite foil. In these cases, the hydrogen is derived from the matrix as evidenced by abundant (M + HD){sup {center dot}+} ions when deuterated ammonium chloride matrix is employed. The fact that the extent of reduction depends on the primary ion dose establishes that it occurs in the energized selvedge region during ion bombardment. Quinones show behavior similar to that of the heteroaromatic compounds with the important difference that the reduced compound is observed in the protonated ((M + 2H){sup {center dot}+} and (M + 3H){sup +}), silver-cationized ((Ag + M + H){sup {center dot}+} and (Ag + M + 2H){sup +}), and negative ion (M(M + H){sup {minus}}) forms. Proton-initiated (heteroaromatics) and electron-initiated (quinones) reaction mechanisms are proposed to accommodate these results. Hydrogenation is not observed upon bombardment of other heteroaromatics or polycyclic aromatic hydrocarbons.